Streamlining the Multi-Disciplinary Team Meeting: The Introduction of Robust Pre-Preparation Methods and Its Effect on the Length of Case Discussions - Merker L; Conroy S; El-Wakeel H; Laurence N (Journal of Multidisciplinary Healthcare, 2023)
Louise Merker,* Soraya Conroy,* Hassan El-Wakeel, Nicola Laurence Department of Breast Surgery, Royal United Hospital, Bath, UK*These authors contributed equally to this workCorrespondence: Louise Merker; Soraya Conroy, Email lmerker@doctors.org.uk; Soraya.conroy@nhs.netIntroduction: The multidisciplinary team (MDT) approach has long been considered the optimal way in which to deliver a high standard of care to patients with breast cancer. With a growing number of patients and ever-increasing complexity of cases, the strain on time and resource of the MDT is becoming increasingly evident. It is therefore essential that local hospital departments adapt their MDT processes to better streamline discussions and optimise efficiency. The Royal United Hospital in Bath is a district general hospital in the UK. Approximately 500 patients with cancers are treated annually, and the MDT discusses approximately 60 patients per week.Methods: To improve our MDT meeting processes and increase productivity, we created a concise MDT template using Microsoft Access™: giving all clinicians the ability to add patients and information in real time. We also allocated weekly preparation time whereby a senior clinician ensured all patients were prepared prior to the meeting with results and potential outcomes prepopulated where possible.Results: We recorded the time spent discussing patients during 6 MDT meetings before and after implementation of changes. Cases were classified by pathology category to determine if there were differences following the preparation changes. Overall, we significantly reduced our average MDT discussion time (p=0.02). We significantly reduced average discussion time in postoperative malignant cases (p< 0.0006) and expected benign core biopsy cases (p< 0.0047), allowing appropriate redistribution of time towards discussion of more complex cases, reflected by the significant increase in time spent discussing complex radiology cases (p< 0.025).Conclusion: We offer an effective method for improving the MDT meeting preparation and presentation by ensuring each patient is appropriately prepared prior to the meeting, and outcomes for those simple cases are already prepopulated. This creates additional time within the meeting to discuss more complex clinical cases while allowing all members of the team an opportunity to discuss all patients if needed.Keywords: breast cancer, multidisciplinary team, MDT, service evaluation, streamlining